2003
DOI: 10.1101/gr.578503
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of the Primary Sex-Determining Locus in Salmonid Fishes

Abstract: We compared the Y-chromosome linkage maps for four salmonid species (Arctic charr, Salvelinus alpinus; Atlantic salmon, Salmo salar; brown trout, Salmo trutta; and rainbow trout, Oncorhynchus mykiss) and a putative Y-linked marker from lake trout (Salvelinus namaycush). These species represent the three major genera within the subfamily Salmoninae of the Salmonidae. The data clearly demonstrate that different Y-chromosomes have evolved in each of the species. Arrangements of markers proximal to the sex-determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
222
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(239 citation statements)
references
References 70 publications
12
222
2
3
Order By: Relevance
“…Ssa202DU is tightly linked to the sex-determining locus (approx. 4 cM) on the Atlantic salmon linkage map (Woram et al, 2003) and paternal allelic segregation at Ssa202DU was assumed to result in a reasonable estimation of progeny sex type. Using allelic segregation at a sex-linked marker cannot identify males versus females, but puts fish into two categories that correspond to different sexes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ssa202DU is tightly linked to the sex-determining locus (approx. 4 cM) on the Atlantic salmon linkage map (Woram et al, 2003) and paternal allelic segregation at Ssa202DU was assumed to result in a reasonable estimation of progeny sex type. Using allelic segregation at a sex-linked marker cannot identify males versus females, but puts fish into two categories that correspond to different sexes.…”
Section: Methodsmentioning
confidence: 99%
“…Linkage maps have been developed for several salmonid fishes, including rainbow trout (RT; Oncorhynchus mykiss) (Young et al, 1998;Sakamoto et al, 2000;Nichols et al, 2003), Arctic charr (AC; Salvelinus alpinus) (Woram et al, 2004), and Atlantic salmon (Salmo salar) (Gilbey et al, 2004;Moen et al, 2004). Despite the extensive karyotypic rearrangements within the tetraploid salmonids (Hartley, 1987;Phillips and Rab, 2001) since their evolution from a diploid ancestor 25-100 MYA (Allendorf and Thorgaard, 1984), microsatellite markers have been able to identify chromosomal regions that are homologous across species (Woram et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data actually confirm that sex chromosomes of O. niloticus, although identified by in situ hybridation techniques, are still weakly differentiated [12,13], and that sex determining genes can be localised on other chromosomes [14]. In salmonids, where the male is generally considered as the heterogametic sex, the determining locus can be situated on different chromosomes depending on the species [15], and other loci can also play a role [16]. Such weak differentiation of sex chromosomes may probably explain that viable abnormal new genotypes YY can be obtained relatively easily through various procedures, such as autofertilisation in hermaphroditic rainbow trout obtained by estrogenic treatment [17].…”
Section: Sexualitymentioning
confidence: 99%
“…Recent studies have shown that the sex chromosomes in two medaka-related species, O. luzonensis and O. dancena, are homologous to different autosomes in medaka Tanaka et al, 2007). Similar phenomena have been observed in salmonids and sticklebacks, suggesting that sex chromosomes have changed frequently in fish (Woram et al, 2003;Peichel et al, 2004;Phillips et al, 2007). In the Japanese frog, Rana rugosa, two distinct sex chromosome types, XX/ XY and ZZ/ZW, were observed in the same species (Miura et al, 1998).…”
Section: Plasticity Of Sex Chromosomes In Lower Vertebratesmentioning
confidence: 54%
“…Many species of fish and amphibians, including medaka, have homomorphic sex chromosomes. Recently, several comparative studies have provided evidence that different sex chromosomes and sex-determining systems have evolved in closely related fish species (Woram et al, 2003;Peichel et al, 2004;Takehana et al, 2007) and in the same species of frog (Ogata et al, 2003). The present results show that in vertebrates possessing homomorphic sex chromosomes, autosomes can easily become sex chromosomes.…”
Section: Introductionmentioning
confidence: 99%